Transadaptation and Validation of the Telugu Version of the Dysphagia Handicap Index - Dasari, Philemon Benison; Verma, Himanshu; Madishetty, Harisha; Pagidimarri, Jothirmai; Balaji, Janaki (Seminars in Speech and Language, 2023)
Dysphagia Handicap Index (DHI) is a clinically effective, concise, and user-friendly tool for assessing the functional impact of dysphagia in clinical populations. The present study aims to trans-adapt the DHI in the Telugu language and assesses its psychometric properties. The present study was conducted in two phases. The first phase includes translating and adapting the DHI tool into Telugu (T-DHI). The second phase includes an analysis of the psychometric properties of the trans-adapted Telugu version of the DHI. The DHI was translated into the Telugu language using the forward–backward translation method. The psychometric analysis was done on 100 participants. All the participants underwent a detailed clinical swallow examination after filling the T-DHI. The overall internal consistency and Guttmann split-half reliability for the Telugu version of the DHI were good. The correlation between the T-DHI subscales and the self-perceived severity of dysphagia was found to be high. The comparison of the T-DHI scores of the control and experimental groups revealed a significant difference. The T-DHI is a reliable and valid tool to assess the quality of life of the Telugu-speaking dysphagia population.
Keywords: dysphagia; Dysphagia Handicap Index; transadaptation; Telugu